Manajemen Strategi Pembelajaran Tahfidz Al-Qur’an dalam Meningkatkan Kualitas Hafalan Santri di Pondok Pesantren - Sodik, Mohamad; Nur Syayidah, Laily; Fadilah, Al Imroatul (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Currently, interest in memorizing the Al-Qur'an continues to increase, resulting in the emergence of educational institutions that organize tahfidz programs. However, in reality, there are still many memorizers of the Qur'an who complain that memorizing the Qur'an is difficult. This is caused by disturbances from within the self, namely from within the soul and disturbances from the environment. A good method will make it easier to memorize and help students not get bored in the memorization process. This research uses descriptive-analytical research, the data obtained are the results of observations, interviews, taking pictures, document analysis, and field notes. The results of this research are the Hifdzil Jadid Management learning strategy (new memorization) in improving the quality of student memorization at the Riyadhus Samawi Blitar Islamic Boarding School by using various strategies including using Tilawati reading and carrying out memorization. The management method/strategy used by caregivers is to give freedom to all students to use any method/method to make it easier to memorize, sometimes using the talaqqi method, Murojaah hifdzil Jadid and Murojaah hifdzil qodim, but before that, they are required to memorize 15 long letters. such as Surah Al-Baqorah, Ali Imran, An-Nisa', Al-Maidah, Al-An'am, Al-A'raf, At-Taubah, Yusuf, Maryam, Al-Waqi'ah, An-Nahl, Yasin, Al-Isro', Al-Kahfi, and As-Su'ara'. By memorizing long letters, the students will be encouraged to memorize shorter letters which will make them aware that they are capable of memorizing so they will be encouraged to memorize 30 Juz.